Evaluation of a Rapid Diagnostic Test (TUBEX-TF) for Diagnosis of Enteric Fever - Riddhi Singh; Nikhil Raj; Sangeeta Singh; Jyotsna Agarwal; Jaya Garg (Archives of Medicine and Health Sciences)
Background and Aim: Enteric fever is a systemic febrile disease caused by Salmonella enterica serovars Typhi and Paratyphi. Culture provides a conclusive diagnosis of enteric fever. The main difficulties are a longer turnaround time and practicality in a developing nation with a huge population. The two RDTs that are now most often used are TUBEX-TF and Enterocheck-WB, where TUBEX-TF can identify IgM antibodies against S. Typhi and S. Paratyphi which are anti-O9 and anti-O2. The aim of this study was to evaluate the performance of the TUBEX-TF test in a typhoid fever endemic area of North India. Materials and Methods: In this cross-sectional study, we have performed TUBEX-TF, Enterocheck-WB /Immuno-chromatographic card test, Enzyme linked immunosorbent assay (ELISA), and Widal tests on the sera of 94 clinically suspected cases of enteric fever It was a cross-sectional comparative study that was carried out at a tertiary care institute in North India. In the present study, the ELISA test was taken as a comparative reference test. Results: ELISA, TUBEX-TF, Widal, and Immunochromatographic card test were performed on serum samples collected from 94 clinically suspected enteric fever cases, in which 50(53.19%) were positive by ELISA, 45 (47.87%) were positive by TUBEX- TF, 40 (42.5%) were positive by Typhidot and 19 (20.2%) were positive by Widal. For evaluation of TUBEX-TF, sensitivity specificity, diagnostic accuracy, positive predictive and negative predictive values, a comparison with IgM Anti-LPS ELISA test results was performed & it was found 75%,79.55%,80%,74.47%, and 77.17% respectively. Conclusion: We conclude that the TUBEX-TF test has a greater sensitivity and specificity than other rapid tests currently on the market. It is a simple, rapid test to diagnose enteric fever. The necessity for large-scale research to evaluate TUBEX-TF is necessary due to interviewer variances so that it can become a novel RDT test for the diagnosis of enteric fever.